A study on customer satisfaction towards service provided by Tabung Haji Klang District / Md Azmi Haron - Haron, Md Azmi (Faculty of Business and Management, 2001)
The Pilgrims Fund Board (Lembaga Tabung Haji) was established with the main objective of providing quality products and services to the customers. Its main function is to provide services to Muslims to keep their money in their endeavor to perform the Haji at Holy Land (Makkah) through concepts of Islamic operation and non-Riba’ benefit.